Suppression of p53-inducible gene 3 is significant for glioblastoma progression and predicts poor patient prognosis - Jishu Quan; Yong Li; Meihua Jin; Dunfu Chen; Xuezhe Yin; Ming Jin (Tumor Biology)
Glioblastoma is the most malignant and invasive brain tumor with extremely poor prognosis. p53-inducible gene 3, a downstream molecule of the tumor suppressor p53, has been found involved in apoptosis and oxidative stress response. However, the functions of p53-inducible gene 3(PIG3) in cancer are far from clear including glioblastoma. In this study, we found that p53-inducible gene 3 expression was suppressed in glioblastoma tissues compared with normal tissues. And the expression of p53-inducible gene 3 was significantly associated with the World Health Organization grade. Patients with high p53-inducible gene 3 expression have a significantly longer median survival time (15 months) than those with low p53-inducible gene 3 expression (8 months). According to Cox regression analysis, p53-inducible gene 3 was an independent prognostic factor with multivariate hazard ratio of 0.578 (95% confidence interval, 0.352–0.947; p  = 0.030) for overall survival. Additionally, gain and loss of function experiments showed that knockdown of p53-inducible gene 3 significantly increased the proliferation and invasion ability of glioblastoma cells while overexpression of p53-inducible gene 3 inhibited the proliferation and invasion ability. The results of in vivo glioblastoma models further confirmed that p53-inducible gene 3 suppression promoted glioblastoma progression. Altogether, our data suggest that high expression of p53-inducible gene 3 is significant for glioblastoma inhibition and p53-inducible gene 3 independently indicates good prognosis in patients, which might be a novel prognostic biomarker or potential therapeutic target in glioblastoma.